Unexpectedly High False-Positive Rates for Haemophilus influenzae Using a Meningoencephalitis Syndromic PCR Panel in Two Tertiary Centers - Zanella, Marie-Céline; Cherkaoui, Abdessalam; Hinic, Vladimira; Renzi, Gesuele; Goldenberger, Daniel; Egli, Adrian; Schrenzel, Jacques (Frontiers in Cellular and Infection Microbiology, 2021)
False-positive results in the diagnostic of meningitis and encephalitis pose important challenges. This study aimed to determine false-positive rates for Haemophilus influenzae in cerebrospinal fluids evaluated by the BioFire FilmArray® Meningitis/Encephalitis Panel. We conducted a retrospective study of all H. influenzae-positive FilmArray®. Meningitis/Encephalitis Panel results from June 2016 to October 2019 in two Swiss university hospitals. Cases were classified as true positive, likely true-positive and likely false-positive results according to cerebrospinal fluid culture, H. influenzae-specific quantitative real-time PCR (qPCR), and Gram staining, as well as culture of other materials. We performed 3,082 panels corresponding to 2,895 patients: 0.6% of samples (18/3,082) were positive for H. influenzae. Culture and H. influenzae-specific qPCR were performed on 17/18 (94.4%) and 3/18 (16.7%) cerebrospinal fluid samples, respectively; qPCR was negative in all cases. Among 17 samples sent for culture, 10 concerned patients not treated with antibiotics prior to lumbar puncture. Only 1/17 revealed growth of H. influenzae and was classified as a true positive. We further classified 3/18 (16.7%) cases with the identification of Gram-negative rods in the cerebrospinal fluid or positive blood cultures for H. influenzae as likely true-positive and 14/18 (77.8%) cases as likely false-positive. Diagnostic results should always be interpreted together with the clinical presentation, cerebrospinal fluid analysis and other available microbiological results. All H. influenzae-positive results should be viewed with special caution and a H. influenzae-specific qPCR should be systematically considered.